PENGARUH LABEL HALAL, PENDAPATAN, DAN GAYA HIDUP TERHADAP MINAT MEMBELI MIE GACOAN PADA MASYARAKAT MUSLIM DI DKI JAKARTA - Izza Fahmi Khoiruman Ramadhan (2023)
Food and beverages are currently one of the businesses that are of interest to entrepreneurs in Indonesia, one of which is DKI Jakarta, because humans really need food and drinks for their survival. One of the food products that people are interested in is processed noodle products. Based on data available on the BPJPH website, out of 171,065 products in DKI Jakarta, only 10,862 products have halal certification. This study focuses on the influence of the halal label, income, and lifestyle on the intention to buy mie gacoan in the Muslim community in DKI Jakarta. The population of this study is the Muslim community in DKI Jakarta who know about mie gacoan restaurants. Sampling method using non-probability sampling technique with purposive sampling method. The approach used is quantitative. Questionnaires are used as data collection techniques. Partial Least Square is used as a data analysis technique. The data test uses the outer and inner models. The result of the r-square value obtained is 0.278. It can be said that the independent variables in this study that is halal label, income, and lifestyle, are able to explain 27.8% of buying interest as the dependent variable. With the remaining 72.2% explained in other variables not included in this study. The results of the hypothesis test are that the halal label has no effect on purchase intention, income has no effect on purchase intention, and lifestyle has an effect on purchase intention.